2009
DOI: 10.3923/pjbs.2009.929.933
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P27, Ki67 and P53 in Squamous Cell Carcinoma, Actinic Keratosis and Bowen Disease

Abstract: This study aims at evaluating the expression of P27, Ki67 and P53 in Squamous Cell Carcinoma (SCC), Actinic Keratosis (AK) and Bowen Disease (BD) specimens. In an analytic-descriptive setting, skin biopsy specimens of 45 patients were evaluated in three 15-case groups including BD, AK and SCC specimens. Fifteen normal skin biopsy specimens were obtained and used as the control group. Immunohistochemical staining was performed in all the specimens and the expression rates and patterns of Ki67, P27 and P53 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Cell proliferation, estimated by rate of Ki67-positive cells, is found to increase according to CSCC stages, from sun-exposed skin to SK [12], from normal skin to SCC [35] and from SK to iSCC [36]. However, some authors have found that Ki67 imunoexpression is higher in SK when compared to SCC [62][63][64], suggesting that Ki67 imunoexpression may not differentiate degree of CSSC malignancy. Interestingly, in the current study there were no significant differences in Ki67LI between groups.…”
Section: Discussionmentioning
confidence: 98%
“…Cell proliferation, estimated by rate of Ki67-positive cells, is found to increase according to CSCC stages, from sun-exposed skin to SK [12], from normal skin to SCC [35] and from SK to iSCC [36]. However, some authors have found that Ki67 imunoexpression is higher in SK when compared to SCC [62][63][64], suggesting that Ki67 imunoexpression may not differentiate degree of CSSC malignancy. Interestingly, in the current study there were no significant differences in Ki67LI between groups.…”
Section: Discussionmentioning
confidence: 98%
“…Ki67 nuclear expression has previously been studied in skin neoplasms and is seen in AK, Bowen disease, SCC and basal cell carcinoma. It indicates the epithelium proliferation rate and patterned expression in the epidermis for each neoplasm . To date, there is no study describing Ki67 expression in SFC activity.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to discriminate SCC variants based on distinct molecular profiles is of great importance when assessing the risk of progression, as well as the clinical management, of patients with cSCC (13). While immunohistochemistry and western blot studies have identified several abundant proteins differentially expressed between cSCC, actinic keratosis (AK) and Bowen's disease lesions, including cyclin-dependent kinase inhibitor 1B (p27), TP53 (14)(15)(16), serpin A1 (SERPINA1) (17); matrix metalloproteinase (MMP)-2, -7, -9 and -13 (16,18,19); c-myc protein (C-MYC) (20); tenascin-C (TNC) (21); and complement factor-I (CFI) and complement factor-H (CFH) (22,23), these markers have not been useful for classifying cSCC subtypes into clinically meaningful categories. The need for comprehensive molecular profiling of cSCC is clear (24).…”
mentioning
confidence: 99%